SIKAP CINTA TANAH AIR MELALUI KELOMPOK PADUAN SUARA PADA SISWA KELAS VII DI SMP NEGERI 2 ALALAK - Mis Erna Fauziah (Universitas Lambung Mangkurat, 2017)
The purpose of research is intended to realize the love of the homeland can be done in the family, school and community. Currently due to the influence of globalization, many Indonesian people are more proud of the culture owned by other nations. The type of research intended here is the type of field research (field research) with a quantitative approach. Field research is a study to obtain the correct data occurs in the field. Data collection with sample probability technique. The research sample is students and students of grade VII selected based on interests and talents for the choir group at SMPN 2 Alalak which amounted to 30 people.Based on the data questionnaires questioning attitude of homeland love of the students conducted three times, from 30 students at the beginning of observation obtained 24 students into the category very good, 4 entered in good category, 1 student is good enough and 1 again entered the category less good, but at the end of observation To 25 students fall into very good category and 5 students fall into either category. In 3 times the implementation of the results obtained is always increased because the teacher as a mentor and mentor routinely explain and motivate students. Prepared planning at the beginning of the school year and the implementation of the program in accordance with the work program resulted in a good and positive homeland love assessment for students who follow the extracurricular activities of choir in SMP Negeri 2 Alalak. Extracurricular activities are beneficial for students in particular and schools in general. Diligent in attending various extrskurikuler activities in school, which is certainly tailored to the talents and interests of students themselves. The existence of fit between activities with talent and interest will add motivation and spirit of students to follow the activity. Keywords: Attitudes, love of the homeland, and choir.Tujuan penelitiani dimaksudkan untuk mewujudkan cinta tanah air dapat dilakukan dilingkungan keluarga, sekolah dan masyarakat. Saat ini akibat pengaruh globalisasi, banyak masyarakat Indonesia lebih bangga terhadap kebudayaan yang dimiliki oleh bangsa lain. Jenis penelitian yang dimaksudkan disini adalah jenis penelitian lapangan (field research) dengan pendekatan kuantitatif. Penelitian lapangan merupakan suatu penelitian untuk memperoleh data yang benar terjadi di lapangan. Pengambilan data dengan teknik probabilitas sampel.Adapun sampel penelitian adalah siswa dan siswi kelas VII yang dipilih berdasarkan minat dan bakat untuk kelompok paduan suara di SMPN 2 Alalak yang berjumlah 30 orang.Berdasarkan data isian kuesioner sikap cinta tanah air dari siswa yang dilakukan sebanyak tiga kali, dari 30 siswa diawal observasi diperoleh 24 siswa masuk kategori sangat baik, 4 masuk dalam kategori baik, 1 siswa cukup baik dan 1 lagi masuk kategori kurang baik, tetapi diakhir observasi menjadi 25 siswa masuk dalam kategori sangat baik dan 5 siswa masuk dalam kategori baik. Dalam 3 kali pelaksanaan hasil yang diperoleh selalu meningkat karena guru selaku pembina dan pembimbing secara rutin menjelaskan serta memotivasi siswa.Perencanaan yang sudah terprogram pada awal tahun ajaran yang sudah dipersiapkan dari sekolah dan pelaksanaan yang dijalankan sesuai dengan program kerja menghasilkan penilaian cinta tanah air yang baik dan positif bagi siswa yang mengikuti kegiatan ekstrakurikuler paduan suara di SMP Negeri 2 Alalak. Kegiatan ekstrakurikuler yang bermanfaat bagi siswa khususnya dan sekolah pada umumnya. Rajin dalam mengikuti berbagai kegiatan ekstrskurikuler di sekolah, yang tentunya disesuaikan dengan bakat dan minat siswa itu sendiri. Adanya kesesuain antara kegiatan dengan bakat dan minat akan menambah motivasi dan semangat siswa untuk mengikuti kegiatan tersebut.Kata Kunci: Sikap, cinta tanah air, dan paduan suara.